ІЛЮСТРАТИВНИЙ МАТЕРІАЛ ЯК ЗАСІБ АКТИВІЗАЦІЇ ПІЗНАВАЛЬНОЇ ДІЯЛЬНОСТІ МОЛОДШИХ ШКОЛЯРІВ НА УРОКАХ ЧИТАННЯ (Педагогіка вищої та середньої школи, 2022)
The article examines the influence of extra textual means on intensification o f primary school children's cognitive activity on lessons dedicated to reading.